Aktivitas Komunikator Politik Partai Gerindra dalam Peningkatan Perolehan Suara pada Pemilu 2024 di Kota Pekanbaru - Widiastuti, Ade (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2024)
This research analyzes Gerindra Party's political communication strategy in increasing political participation through social media, focusing on young voters and political communicator activities. Using a descriptive qualitative approach, this research aims to describe and understand social phenomena from the perspective of participants, with a case study analysis model. The results show that Gerindra Party targets young voters as part of its electoral strategy. The party actively engages young voters through in-person and online discussion activities, and interacts on social media using casual language that is easily understood by the millennial generation. The activities of Gerindra's political communicators on social media aim to bridge the gap between young voters and political parties, as well as to build personal closeness. political parties, as well as building personal closeness. In addition, the announcement regarding Gerindra's legislative candidates for the Pekanbaru City DPRD in the 2024 Election is disseminated transparently through official letters. Overall, political communication strategy implemented by the Gerindra Party, through the activities of effective political communicators on social media, succeeded in increasing activities on social media, succeeded in increasing political participation, especially among young voters, political participation, especially among young voters.